(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
In this article I expose some critical points about museum evaluation, from anthropology, focused on non-formal education. A first aspect refers to the false dilemma raised in public studies of an opposition between research and evaluation, considering that the second corresponds to a type of applied research, which meets the basic requirements and conditions of any research. Research that has the character of being comparative, an aspect that is not always clearly stated. Immediately I point out the importance of the context, little attended, in the educational, cultural and museum fields. Later, I recommend using clear and explicit definitions of the aspects to be evaluated, otherwise confusing or doubtful results are generated. A next point - linked to the central theme of the XVII Camarilla - corresponds to the difficult task of evaluating non-formal education that occurs in museums. Items that together will express the importance of the anthropological perspective, in conceptual and methodological terms. Finally, I close the text with a final reflection.